2022
DOI: 10.3390/ijms24010244
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Transposable Elements in Human Skeletal Muscle Fibers upon Statin Treatment

Abstract: High cholesterol levels have been linked to a high risk of cardiovascular diseases, and preventative pharmacological care to lower cholesterol levels is critically important. Statins, which are hydroxymethylglutaryl-coenzyme A (HMG-CoA) reductase inhibitors, are drugs used to reduce the endogenous cholesterol synthesis, thus minimizing its pathophysiological effects. Despite the proven benefits, statins therapy is known to cause a number of skeletal muscle disorders, including myalgia, myopathy and myositis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…A recent review has revealed that several types of stress can modulate the expression of specific Drosophila TEs, with repressed TEs outnumbering induced ones among these differentially expressed elements (30). This pattern has also been observed in vertebrates, such as humans, where there are more repressed than induced TEs after exposure to some chemical compounds, such as Simvastatin (139) and short-term treatment with Morphine (140). Classical theories argue that TE induction after stress exposure acts as a force that can generate diversity, consequently contributing to the species’ adaptation to changing environments.…”
Section: Discussionmentioning
confidence: 62%
“…A recent review has revealed that several types of stress can modulate the expression of specific Drosophila TEs, with repressed TEs outnumbering induced ones among these differentially expressed elements (30). This pattern has also been observed in vertebrates, such as humans, where there are more repressed than induced TEs after exposure to some chemical compounds, such as Simvastatin (139) and short-term treatment with Morphine (140). Classical theories argue that TE induction after stress exposure acts as a force that can generate diversity, consequently contributing to the species’ adaptation to changing environments.…”
Section: Discussionmentioning
confidence: 62%
“…Estrogens, which are involved in cholesterol and lipid metabolism, have also been found to drive changes in repeat expression, and the receptors for both estrogens and androgens are believed to bind repeat DNA [ 50 , 51 ]. Pharmacological inhibition of the mitochondrial respiratory chain and pharmacological reduction of endogenous cholesterol synthesis have also been shown to induce changes in L1 protein levels or repeat expression more broadly [ 52 , 53 ]. GSEA with the GO Biological Process gene sets ( Fig 3F and Sheet X in S4 Table ) and the Reactome gene sets ( Fig 3G and Sheet Y in S4 Table ) also identified several metabolism-related pathways including “ATP metabolic process”, “Generation of precursor metabolites and energy”, and “metabolism of amino acids and derivatives”.…”
Section: Resultsmentioning
confidence: 99%
“…Estrogens, which are involved in cholesterol and lipid metabolism, have been found to drive changes in repeat expression, and the receptors for both estrogens and androgens are believed to bind repeat DNA (Sampathkumar et al 2020; Wahl et al 2020). Pharmacological inhibition of the mitochondrial respiratory chain and pharmacological reduction of endogenous cholesterol synthesis have also been shown to induce changes in L1 protein levels or repeat expression more broadly (Baeken et al 2020; Valdebenito-Maturana et al 2023). GSEA with the GO Biological Process gene sets ( Figure 3F , Supplementary Table S4X ) and the Reactome gene sets ( Figure 3F , Supplementary Table S3Y ) also identified several metabolism-related pathways including “ATP metabolic process”, “Generation of precursor metabolites and energy”, and “metabolism of amino acids and derivatives”.…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacological inhibition of the mitochondrial respiratory chain and pharmacological reduction of endogenous cholesterol synthesis have also been shown to induce changes in L1 protein levels or repeat expression more broadly [34,35]. GSEA with the GO Biological Process gene sets (Figure 3E, Supplementary Table S3T) and the Reactome gene sets (Figure 3F, Supplementary Table S3U) also identified several metabolism-related pathways including "ATP metabolic process", "Generation of precursor metabolites and energy", and "metabolism of amino acids and derivatives".…”
Section: -S3r)mentioning
confidence: 99%